3D spongy nanofiber structure Fe–NC catalysts built by a graphene regulated electrospinning method. Issue 46 (6th May 2020) - Ding, Weiyuan; Yu, Hongquan; Tang, Yu; Li, Zhuxin; Liu, Bijiao; Liu, Dechong; Wang, Yuyu; Liu, Shu hong; Zhao, Hong; Mandler, Daniel
Abstract : A Fe–NC catalyst containing carbon nanotubes, mesopores and macropores with a measurable 3D framework structure was prepared by electrospinning. Abstract : 3D spongy nanofiber structure Fe–NC catalysts were constructed by a graphene regulated electrospinning method. The framework of the catalysts was reconstructed into carbon nanotubes, mesopores and macropores, and most of the Fe3 C is converted to Fe2 N during the calcination process. All catalysts showed better electrocatalytic performances than commercial Pt/C.